Thioglycolic acid as a Reagent for Trace Determination of Zn(II), Cd(II) and Hg(II) - Khatkar, S.P.; Devi, Rekha (Asian Journal of Chemistry, 2010)
Amperometric determination of Zn(II), Cd(II) and Hg(II) was carried out with the help of thioglycolic acid (TGA) at d.m.e. in 0.1 M NH3 + 0.1 M NH4Cl, 0.1 M Na2CO3 + 0.1 M NaHCO3 and 0.1 M KCl medium, respectively. Metal ion solutions were used as titrant in all the cases (anodic titrations). Titrations of Hg(II) solutions using acid as titrant (cathodic titrations) were also carried out successfully. Metal species-TGA stoichiometry obtained was 1 : 2 in all the cases. Solutions as dilute as 6.539 ppm (Zn), 11.24 ppm (Cd) and 10.03 ppm (Hg) were estimated with high degree of accuracy. Tolerance limit for foreign ions has also been worked out.